Liputan Pilihan Raya Kecil Permatang Pauh: Analisis Teori Penentuan Agenda Dalam Akhbar Arus Perdana dan Alternatif Terpilih - Mohd Hilmi, Hamzah (2012)
This study was conducted to identify issues, themes and news directions featured in Utusan Malaysia, Berita Harian, Harakah and Suara Keadilan during the 2008 Permatang Pauh by-election campaign. Agenda Setting Theory was used as the theoretical framework underlying this research. Four hundred and seventy four (474) news articles produced by the four newspapers for the above mentioned election were analyzed using both quantitative and qualitative approaches. The qualitative analysis carried out, in particular, through the tree nodes analysis technique revealed 11 issues and three themes from the newspapers studied. The emerging issues were 1) government formation, 2) education, 3) candidates, 4) ethnic, 5) elections, 6) media, 7) ruling party, 8) Pakatan Rakyat, 9) development, 10) religion and 11) security. The issues were then categorized into three themes, namely, politics, economics and social. The findings showed that, in terms of frequency, the most prominent issue is the issue of candidates. Politics, on the other hand, is the most profound theme where the frequency of the newspaper features is concerned. The study also found that the direction of the news reporting varies. Utusan Malaysia and Berita Harian were inclined to report negatively on Pakatan Rakyat while Suara Keadilan and Harakah reported negatively towards the ruling government. The latter newspapers, however, were favourable in their reports on the Pakatan Rakyat. The findings based on Agenda Setting Theory indicate that the company shareholders and the newspaper editors had a heavy influence on the news reporting made by the four newspapers studied.